Transformations of the New Germany - Starkman, R.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
This collection demonstrates the persistence of the initial anxieties about a united Germany and its rapid absorption of the German Democratic Republic, and also suggests a potential optimism that, despite much contemporary domestic disenchantment, the new Germany continues to thrive as a European democracy endeavouring to confront its past.
Keywords: Europe, Central—History.; Europe—History.; History, Modern; World politics; World history; History of Germany and Central Europe; European History; Modern History; Political History; World History, Global and Transnational History